2019
DOI: 10.1038/s41598-019-46116-9
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory role of NLRP3 inflammasome in experimental sterile corneal inflammation

Abstract: We evaluated the role of NLR family pyrin domain containing 3 (NLRP3) inflammasome in sterile corneal inflammation caused by lipopolysaccharide (LPS) or alkali burns in C57BL6 mice or NLRP3 KO ( Nlrp3 −/− ) mice. Various molecules related to the NLRP3 inflammasome were upregulated in C57BL6 mice after both alkali burn injury and LPS treatment. After alkali burn injury, the corneal opacity grade was significantly reduced in Nlrp3 −/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…Subsequently, NOD1, NOD2, NLRP1, NLRP3 were shown to be regulated during bacterial or fungal infections in humans [68][69][70] and mouse [71,72] cornea. However, several reports suggested the source of the NLR proteins to be derived from infiltrated neutrophils or monocytes at the site of infection [73][74][75]. In dry eye conditions, human patients with environment-induced dry eye [76], murine models of dry eye [77,78], and alkali-burned mice [79] all showed increased mRNA levels of NLRP3 in their conjunctival epithelium.…”
Section: Nod-like Receptors In the Ocular Tissuesmentioning
confidence: 99%
“…Subsequently, NOD1, NOD2, NLRP1, NLRP3 were shown to be regulated during bacterial or fungal infections in humans [68][69][70] and mouse [71,72] cornea. However, several reports suggested the source of the NLR proteins to be derived from infiltrated neutrophils or monocytes at the site of infection [73][74][75]. In dry eye conditions, human patients with environment-induced dry eye [76], murine models of dry eye [77,78], and alkali-burned mice [79] all showed increased mRNA levels of NLRP3 in their conjunctival epithelium.…”
Section: Nod-like Receptors In the Ocular Tissuesmentioning
confidence: 99%
“…After an acute corneal sterile injury, inflammatory cells exaggerated damages by releasing the influx of various deleterious cytokines and leukocytes. 15 As maintainers of immunological homeostasis, Tregs have been reported to recruit to corneas in virus-infected keratitis models. 16 Corroborating the findings of fluorescent activated cell sorting (FACS) analyses, Tregs infiltrated the local site of acute corneal alkali burn and continuously accumulated ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In combination with the aptamer apoptosis-associated speck-like protein containing CARD (ASC), it mediates the activation of cysteine aspartate proteinase-1 (caspase-1) and the secretion of proinflammatory cytokines including IL-1β and IL-18. 21,51,[58][59][60][61][62][63][64] Activation signals can be provided by a variety of extracellular stimuli or molecules, including microbial toxins, as well as cellular damage events, such as mitochondrial dysfunction and ROS production. Among them, intracellular ROS and NLRP3 inflammasomes are mutually promoted.…”
Section: Discussionmentioning
confidence: 99%
“… 51 , 58 , 65 Studies have shown that both corneal and conjunctival epithelial cells harbor functional NLRP3 inflammasomes. 60 , 66 Due to the difference between infectious and noninfectious lesions, different corneal diseases may be associated with variation in expression of nucleotide binding and oligomerization domain-like receptor (NLR). 67 In our study, the immunofluorescence staining of ASC, caspase-1, and IL-1β of CECs were all enhanced under MNU, whereas they were weakened under H 2 , indicating that the function of NLRP3 inflammasomes could be activated by MNU and inhibited by H 2 .…”
Section: Discussionmentioning
confidence: 99%